Laparoscopic Ureterolithotomy with Concomitant Pyelolithotomy Using Flexible Cystoscope - Sahin, Selcuk; Resorlu, Berkan; Atar, Feyzi Arda; Eksi, Mithat; Sener, Nevzat Can; Tugcu, Volkan (Urology Journal, 2016)
Purpose: To report and discuss the treatment of ipsilateral upper ureteral and renal stones by laparoscopic ureterolithotomy with concomitant pyelolithotomy using flexible cystoscope. Materials and Methods: A total of 19 patients (14 men and 5 women) underwent laparoscopic retroperitoneal ureterolithotomy with concomitant pyelolithotomy using flexible cystoscope through the ureterotomy site. The mean age of the patients was 37.9 (22-61) years. Stones were on the right side in 12, on the left side in 7, and multiple in 6 patients. All ureteral stones were located in the upper ureter. Most renal stones were in the pelvis or in the calices. Results: All procedures were completed laparoscopically without conversion to open surgery. Mean operation duration was 86.5 (range: 80-93) minutes, thus operation duration was prolonged by a mean of 24.4 minutes in patients with concomitant stone extraction. Fifteen cases were treated using flexible cystoscope and a nitinol basket; in the remaining four cases holmium laser lithotripsy was performed. Complete stone clearance was confirmed by postoperative imaging in all patients. Conclusions: Laparoscopic ureterolithotomy with concomitant pyelolithotomy is a feasible and effective technique for patients with large ureteral stone and low renal stone burden.